The Oxford Handbook of Thinking and Reasoning 2012
DOI: 10.1093/oxfordhb/9780199734689.013.0040
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Think: Cognitive Mechanisms of Knowledge Transfer

Abstract: Learning to think is about transfer. The scope of transfer is essentially a knowledge representation question. Experiences during learning can lead to alternative latent representations of the acquired knowledge, not all of which are equally useful. Productive learning facilitates a general representation that yields accurate behavior in a large variety of new situations, thus enabling transfer. This chapter explores two hypotheses. First, learning to think happens in pieces and these pieces, or knowledge comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…The cognitive psychology literature provides certain reasons why simulation tools could help people improve their incorrect mental models. For example, simulation tools may allow users to set specific goals iteratively (Yang et al, 2016); these tools may permit users to experience gradual increases in a problem's complexity (Yasarcan, 2010;Ozgun and Barlas, 2013;; and they may provide analogies and alternative representations to improve learning (Holyoak and Koh, 1987;Gentner et al, 2003;Gonzalez and Wong, 2012;Koedinger and Roll, 2012;Smith and Gentner, 2012;Dutt and Gonzalez, 2013a;2013b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cognitive psychology literature provides certain reasons why simulation tools could help people improve their incorrect mental models. For example, simulation tools may allow users to set specific goals iteratively (Yang et al, 2016); these tools may permit users to experience gradual increases in a problem's complexity (Yasarcan, 2010;Ozgun and Barlas, 2013;; and they may provide analogies and alternative representations to improve learning (Holyoak and Koh, 1987;Gentner et al, 2003;Gonzalez and Wong, 2012;Koedinger and Roll, 2012;Smith and Gentner, 2012;Dutt and Gonzalez, 2013a;2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research in cognitive psychology has shown that experience gained through analogies helps people to learn about stock-and-flow relationships (Koedinger and Roll, 2012;Smith and Gentner, 2012). Thus the use of examples in simulation tools would promote the learning of difficult system dynamics concepts (Gentner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior knowledge has been shown to greatly affect how learners interpret and learn from their class materials (e.g., Rittle-Johnson et al 2009), how well they can implement domain-general problem-solving strategies (see, e.g., Koedinger and Roll 2012;Zimmerman 2000, for reviews), how well they are able to generalize knowledge encoded from earning materials to novel cases or problems (e.g., Carpenter et al 2006) and how well they are prepared for future learning tasks (e.g., Bransford and Schwartz 1999). Further, the degree with which new concepts conflict with the students' prior knowledge (e.g., their naïve theories) is one of the primary determinants of how difficult a concept is to learn (Chi et al 2012;Jacobson et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A learning barrier constantly facing college students lies in the implementation of classroom concepts to solve real-life problems ( Day & Goldstone, 2013 ). Cognitive disassociation between textbook knowledge and decision-making processes often results in educational failure, and thereby hinders career success ( Koedinger & Roll, 2012 ). As virtual reality training rapidly gains popularity in many academic and professional settings worldwide, it is important from both theoretical and practical perspectives to examine the potential eff ects that immersive three-dimensional (3D) virtual reality may have on learning retention and transfer ( Holzinger, Kickmeier-Rust, & Albert, 2009 ;Kalyuga, Renkl, & Paas, 2010 ;Meissner & Bogner, 2012 ;Day & Goldstone, 2013 ).…”
mentioning
confidence: 99%